Pengaruh Pendekatan Whole Language terhadap Prestasi Belajar Siswa Kelas IV di SDN 022 Cicadas Kota Bandung dalam Mata Pelajaran Bahasa Indonesia - Syahidah, Raihana Nurul; Samadi, Mochammad Ramdan; Mulyani, Ani Sri; Subiyono (Prodi PGMI STAI Sabili Bandung, 2024)
This study aims to evaluate the impact of implementing the Whole Language approach on students' learning outcomes in Indonesian language subjects at SDN 022 Cicadas, Class IV. Utilizing a quantitative research method with an experimental design, the study involved two groups: an experimental group employing the Whole Language approach and a control group using conventional methods of lectures and assignments. Data were collected through pre-tests conducted before the intervention and post-tests administered following the intervention to assess changes in students' comprehension. The findings reveal that the experimental group experienced a significant improvement in average post-test scores, increasing from 53.6 to 81.27, whereas the control group showed a more modest increase from 53 to 63.6. These results indicate that the Whole Language approach is more effective in enhancing students' learning outcomes compared to traditional methods. The approach was found to not only improve students' understanding of the material but also enhance their engagement and involvement in the learning process. This study underscores the importance of methodological innovation in achieving superior academic results.